Identifying Critical Tasks in the Kadiri University 4 Floor Building Construction Project Using the Critical Path Method - Ali, Mahardi Kamalika Khusna; Tjendani, Hanie Teki; Witjaksana, Budi (International Journal of Science, Technology & Management, 2024)
This study aims to identify critical tasks in the construction of a 4-floor building at Kadiri University using the Critical Path Method (CPM). The project is planned to be completed within 43 weeks, from October 2023 to August 2024, with a budget of IDR 20,551,534,000. Data collection involved direct site visits for primary data and secondary data from project documentation, including the Cost Budget Plan (RAB) and project schedule. Using Microsoft Project software, a project network was mapped, and CPM analysis was performed to identify the critical path. The analysis revealed that several tasks, such as site cleaning, demolition, temporary project fencing, heavy equipment work, geotechnical work, and various structural works from the 1st to the 5th floors, are on the critical path. These tasks have zero slack time, indicating that any delays will directly impact the overall project timeline. Identifying the critical path is crucial for project managers to prioritize resources and efforts on these tasks to ensure the project stays on schedule. This study underscores the significance of CPM in project management for timely completion and effective resource allocation, providing valuable insights for managing similar construction projects.